1997
DOI: 10.1002/elan.1140091511
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of methylene blue using α‐zirconium phosphate and its application within a reagentless amperometric hydrogen peroxide biosensor

Abstract: A novel H202 sensor was constructed by employing methylene blue (MB) incorporated in a-zirconium phosphate as an electron transfer mediator. Methylene blue was intercalated into a a-zirconium phosphate modified horseradish peroxidase (HRP) immobilization matrix cross-linked on a glassy carbon electrode surface via bovine serum albumin (BSA)-glutaraldehyde. Such a coimmobilization matrix of the mediator and enzyme was formed from a-zirconium phosphate-MB inclusion colloid in which horseradish peroxidase was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…15 The present paper is the first report on the application of GOx immobilized in ZrP for an amperometric glucose sensor. Although Ruan et al 16 reported on a ZrP-based enzyme electrode with peroxidase and a mediator embedded in ZrP, there has been no report on glucose sensors based on GOx embedded in ZrP to our best knowledge. In this study, GOx was intercalated in ZrP according to the method described by Kumar et …”
mentioning
confidence: 98%
“…15 The present paper is the first report on the application of GOx immobilized in ZrP for an amperometric glucose sensor. Although Ruan et al 16 reported on a ZrP-based enzyme electrode with peroxidase and a mediator embedded in ZrP, there has been no report on glucose sensors based on GOx embedded in ZrP to our best knowledge. In this study, GOx was intercalated in ZrP according to the method described by Kumar et …”
mentioning
confidence: 98%
“…23 Owing to these characteristics, a crystalline layered phosphate compound can be used as a matrix for immobilization of electroactive species. 24 This investigation focuses on the electrochemical behavior of copper (II) as it is adsorbed on 4-aminobenzoic acid intercalated calcium phosphate. This newly synthesized compound was first used to prepare a carbon-paste electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, large numbers of peroxidase-based H2O2-sensing electrodes have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Among various heme-containing plant peroxidases, horseradish peroxidase (HRP) has been widely employed in enzyme electrodes, because HRP is relatively stable, cost-effective and commercially available in highly purified form. In addition, the structure and the reaction mechanism of the HRP has been well investigated.…”
Section: Introductionmentioning
confidence: 99%